A Hackney Disciple of the Beast 666: A History in Letters - Josiffe, Christopher (The pomegranate, 2016)
Studies of Aleister Crowley's followers have tended to focus on unconventional or bohemian figures. This article examines a different type of person-Neville Foreman, an insurance clerk and family man who lived in the unfashionable Clapton district of Hackney, East London. Several years' correspondence between Foreman and Crowley sheds light on the profile of a Crowley acolyte from a more conventional background. Whilst Foreman was no bohemian, this lower-middle class office clerk was nonetheless an esoteric seeker. Dissatisfied with his previous explorations in New Thought, Theosophy and Anthroposophy, Foreman arrived at Crowley and Thelema hoping for spiritual guidance and personal development, and also seeking some resolution to his sexual difficulties.